2021
DOI: 10.1136/bmjopen-2021-048888
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of maternal knowledge of neonatal danger signs among postpartum mothers in Southern Ethiopia: institutional-based cross-sectional study

Abstract: Objective The main aim of this study was to assess knowledge of neonatal danger signs and associated factors among postpartum mothers in Southern Ethiopia. Setting Gurage zone, Southern Ethiopia. Study participants A total of 608 postpartum mothers were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…Similarly, the uptake of postnatal care is also identified as a significant predictor of receiving health information on NDSs, in tandem with studies conducted in China [ 29 ], Kenya [ 51 ], Ghana [ 52 ], and Ethiopia [ 19 , 26 , 48 , 53 ]. One possible explanation is that mothers who received postnatal care may have received health education about NDSs from healthcare providers, which is one of the essential components of postpartum visits [ 54 ].…”
Section: Discussionmentioning
confidence: 79%
“…Similarly, the uptake of postnatal care is also identified as a significant predictor of receiving health information on NDSs, in tandem with studies conducted in China [ 29 ], Kenya [ 51 ], Ghana [ 52 ], and Ethiopia [ 19 , 26 , 48 , 53 ]. One possible explanation is that mothers who received postnatal care may have received health education about NDSs from healthcare providers, which is one of the essential components of postpartum visits [ 54 ].…”
Section: Discussionmentioning
confidence: 79%
“…All the articles reported on quantitative cross-sectional studies. Sixteen of the articles were from studies conducted in Ethiopia (Beraki et al, 2020;Yaya Tessema et al, 2023;Leta, 2022;Berhan & Gulema, 2018;Getachew et al, 2022;Berhea et al, 2018;Mose et al, 2021;Hassen & Lelisho, 2022;Mekonnen et al, 2021;Seifu et al, 2020;Guta et al, 2020;Kebede et al, 2020;Tesfaye et al, 2022;Yitayew et al, 2021;Bulto et al, 2019;Degefa, et al, 2019), two each in Kenya (Kiragu et al, 2021;Roney et al, 2021), Tanzania (Msiba et al, 2022;Nchimbi & Joho, 2022), and Rwanda (Batamuriza & Uwingabire, 2020;Deynu & Nutor, 2023), and one each in Sierra Leone (Kanu et al, 2014), Zambia (Chembe & Siziya, 2017), and South Sudan (Meseka et al, 2017). Eight of the articles (Mose et al, 2021;Guta et al, 2020;Kebede et al, 2020;Tesfaye et al, 2022;Yitayew et al, 2021;Bulto et al, 2019;Degefa, et al, 2019;Roney et al, 2021) reported on studies that researched on knowledge of neonatal danger signs (NDS), seven (Leta, 2022;Berhan & Gulema, 2018;Getachew et al, 2022;Berhea, et al, 2018;Msiba, et al, 2022;…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…The individual-level determinants of PNC knowledge include place of residence (Beraki et al, 2020;Mose et al, 2021;Mekonnen et al, 2021;Yitayew, et al, 2021;Deynu & Nutor, 2023), age of the mother (Beraki et al, 2020;Batamuriza & Uwingabire, 2020), age at first pregnancy, marital status (Beraki et al, 2020;Deynu & Nutor, 2023), educational level of the mother (Beraki et al, 2020;Yaya Tessema et al, 2023;Leta, 2022;Getachew et al, 2022;Berhea et al, 2018;Hassen & Lelisho, 2022;Seifu et al, 2020;Yitayew et al, 2021;Bulto et al, 2019;Degefa et al, 2019;Roney et al, 2021;Nchimbi & Joho, 2022;Kanu et al, 2014;Chembe & Siziya, 2017), educational level of the father (Hassen & Lelisho, 2022;Yitayew et al, 2021), and religion of the mother (Getachew et al, 2022). All articles that reported on place of residence as a determinant of PNC knowledge (Beraki et al, 2020;Mose et al, 2021;Mekonnen et al, 2021;Yitayew et al, 2021;Deynu & Nutor, 2023) revealed that those who stayed in urban areas were more likely to have good PNC knowledge compared to those who stayed in rural areas. Two articles (Beraki et al, 2020;Batamuriza & Uwingabire, 2020) revealed that an increase in maternal age was associated with an improvement in PNC knowledge among them.…”
Section: Review Findingsmentioning
confidence: 99%
See 2 more Smart Citations